Strategi Komunikasi Digital Merek Fashion Global dalam Membangun Brand Engagement: (Studi Komparatif Zara, H&M, dan Uniqlo di Media Sosial) - Christine Marry Gabrielle; Andhini Winariyanti (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
Digital transformation has fundamentally changed how fashion brands communicate with consumers. This study analyzes the digital communication strategies of three global fashion brands—Zara, H&M, and Uniqlo—across Instagram, TikTok, Facebook, and YouTube. Using systematic digital observation and descriptive quantitative content analysis, the study monitored the brands’ official social media activities for 14 days, from 6 to 19 December 2025. The analysis covered platform usage frequency, content types, and public response indicators, including views, likes, comments, and shares. The results show that Instagram was the most frequently used platform, accounting for 60% of posts, followed by Facebook at 21%, TikTok at 13.9%, and YouTube at 4.7%. Although TikTok had fewer posts and a smaller follower base, it generated the highest relative level of public engagement. Product-oriented content and tips or tutorials were equally dominant at 38.8% each, while event-related and general or interactive content each represented 11.2%. Each brand also demonstrated a distinct communication orientation: Uniqlo emphasized functional and educational narratives, H&M balanced product promotion with community interaction, and Zara focused on trend-responsive visual product presentation. The findings confirm the importance of aligning platform characteristics, content typology, and brand positioning to maximize brand engagement in the digital fashion industry.